Shipping Routes and Spice Trade in Southeast Sulawesi in the 17th and 18th Century - Susanto Zuhdi (Journal of Maritime Studies and National Integration, 2018)
This paper discusses the dynamics of sea voyage and trade formed in the network of Southeast Sulawesi waters in the 17th and 18th century. Buton was chosen as a port that played the role in that network. Southeast Sulawesi as the concept of region will be positioned in the eastern and southern part of Sulawesi network, and other parts of the Nation. In addition to the strategic location connecting Makassar to North Maluku and Central Maluku, also spices as the commodities transported through this line, Buton has its own trade commodities, such as slaves, and iron tools (knives, machetes). Although it is not in large in numbers, cloves from Buton were also the target of VOC. As a collecting center port, Buton plays a role in the network of "feeder point" ports such as Raha and Tukangbesi Islands (now Wakatobi), with the entrepot, Makassar. The changes after Makassar fell into VOC’s hands has made Buton contributing more as a supplier. Although Buton was an ally of VOC, marked by a contract signed in 1613, but in some respects there was resistance, both openly as Buton War in 1755 and rebel against the ban on growing cloves (extirpation) and illegal trade (sluijkhandel). Literature review and tracking down of primary sources in the form of archives and oral tradition are important steps for further study.